2017
DOI: 10.1136/bmjopen-2016-013889
|View full text |Cite
|
Sign up to set email alerts
|

Association between neighbourhood walkability and metabolic risk factors influenced by physical activity: a cross-sectional study of adults in Toronto, Canada

Abstract: ObjectiveTo determine whether neighbourhood walkability is associated with clinical measures of obesity, hypertension, diabetes and dyslipidaemia in an urban adult population.DesignObservational cross-sectional study.SettingUrban primary care patients.Participants78 023 Toronto residents, aged 18 years and over, who were formally rostered or had at least 2 visits between 2012 and 2014 with a primary care physician participating in the University of Toronto Practice Based Research Network (UTOPIAN), within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…Ten studies investigated the association between neighbourhood walkability and T2DM risk/prevalence. Six studies received a strong quality rating [ 20 , 48 , 57 , 58 , 62 , 65 ]. Six studies observed that highly walkable neighbourhoods were associated with a lower T2DM risk/prevalence [ 19 22 , 45 , 54 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies investigated the association between neighbourhood walkability and T2DM risk/prevalence. Six studies received a strong quality rating [ 20 , 48 , 57 , 58 , 62 , 65 ]. Six studies observed that highly walkable neighbourhoods were associated with a lower T2DM risk/prevalence [ 19 22 , 45 , 54 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have established Walk Score as a validated measure of neighborhood walkability that is associated with cardiometabolic risk factors (such as physical activity, obesity and blood pressure) in a variety of settings, including Toronto 21–24. In the current study, Walk Score was indeed associated with total physical activity in the year prior to pregnancy.…”
Section: Discussionsupporting
confidence: 48%
“…It should be recognized that our data do not rule out any impact of walkability on risk of GDM (however small), particularly since neighborhood design will affect the entire population where even a modest effect can be beneficial for society. Accordingly, these data certainly do not argue against city planning as a societal approach to the T2DM epidemic (as enhanced walkability has been linked to cardiometabolic benefits outside of pregnancy) 2–5 21–24. However, our inability to detect any discernible impact of neighborhood walkability on insulin sensitivity, beta-cell function and glycemia in 1318 pregnant women suggests that the overall effect of urban design on the incidence of GDM may be relatively modest (as compared with its benefits outside of pregnancy).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This could potentially underline obstacles that may be introduced by the build environment. As previous studies have shown an association between living in the most walkable neighborhoods [32] and having a lower BMI in adults of all ages, it see could be interesting to study what may pose barriers to active transportation and to study the effect of those barriers on healthy habits.…”
Section: Discussionmentioning
confidence: 99%